Consanguinity and Its Effect on Morbidity and Congenital Disorders Among Arabs in Israel - Rajech, Sharkia; Esmael, Athamny; Mohamad, Khatib; Ahmad, Sheikh-Muhammad; Abdussalam, Azem; Muhammad, Mahajnah (IntechOpen, 2011)
None